Constructing Individual and Social Piety through the Internalization of Qur'anic Values: A Case Study of Al-Idris Islamic Boarding School - Ahmad Rifqi Nurkhakim; Wahid Hariyanto; Ahmad Sulton (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study investigates the internalization of Qur'anic values in constructing individual and social piety among santri at Al-Idris Islamic Boarding School, Ponorogo. It addresses a research gap in pesantren studies, which often discuss individual piety, social piety, and Qur'anic character formation separately. Using a qualitative case study design, data were collected through participant observation, documentation, and semi-structured interviews with the pesantren caregiver, ustaz, santri, and administrators. Data were analyzed through transcription, open coding, categorization, theme development, data display, triangulation, and conclusion drawing. The findings show that Qur'anic value internalization occurs through three interconnected stages: value transformation, value transaction, and transinternalization. These stages are supported by classical Islamic text learning, tahsin, tahfidz, daily Qur'an recitation, worship habituation, mentoring, educator exemplarity, deliberation, communal service, and socio-religious participation. The novelty of this study lies in proposing an integrative model that connects personal worship discipline with social responsibility within a shared pesantren ecosystem. Theoretically, this study extends value internalization theory by positioning religious character formation as an ecosystemic process shaped by learning, habituation, relationships, exemplarity, and communal culture.